2015
DOI: 10.1002/pat.3687
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Pickering emulsion by use of PCM and SiC and application to preparation of hybrid microcapsules with interfacial polycondensation reaction

Abstract: It was tried to form Pickering emulsion by use of paraffin wax as a phase change material (PCM) and SiC as solid powder and to apply to the preparation of the hybrid microcapsules with the interfacial polycondensation reaction. Pickering emulsion could be formed by stirring PCM and SiC in the continuous water phase. The mean diameter of PCM droplets in the (O/W) emulsion decreased with the added amount of SiC. The SiC weight adhered on the surface of PCM droplets become the maximum in the continuous phase with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…19−21 For instance, Taguchi and partners created hybrid microcapsules via the interfacial polymerization method after producing a Pickering emulsion with paraffin as PCMs and silicon carbide (SiC) as a solid powder. 22 According to the results, MEPCMs with hybrid shells have better heat transmission properties. Pang et al effectively produced microcapsules utilizing polyurea as the shell material after creating a Pickering emulsion using a lignin particle as an emulsion stabilizer.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…19−21 For instance, Taguchi and partners created hybrid microcapsules via the interfacial polymerization method after producing a Pickering emulsion with paraffin as PCMs and silicon carbide (SiC) as a solid powder. 22 According to the results, MEPCMs with hybrid shells have better heat transmission properties. Pang et al effectively produced microcapsules utilizing polyurea as the shell material after creating a Pickering emulsion using a lignin particle as an emulsion stabilizer.…”
Section: Introductionmentioning
confidence: 95%
“…Solid particles commonly used in Pickering emulsions include SiO 2 , TiO 2 , cellulose nanofibers, etc. For instance, Taguchi and partners created hybrid microcapsules via the interfacial polymerization method after producing a Pickering emulsion with paraffin as PCMs and silicon carbide (SiC) as a solid powder . According to the results, MEPCMs with hybrid shells have better heat transmission properties.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the current research regarding PCMs focus on the preparation and investigation of form-stable phase change materials (FSPCMs). [9][10][11] The common FSPCMs are formed by that PCMs incorporated into support materials. The layered or porous structure materials are the candidates for framework of FSPCMs, which including expanded glass, 12 aluminum nitride, 13 silica fume, 14 fly ash, 15 polyethylene 16 and perlite et al 17 Polymer sponge is considered as one of the frameworks for PCMs due to their high porosity, excellent flexibility and lipophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been tried to seal up PCMs, such as microencapsulation, using tank, et al 7,8 But those methods suffer from high cost, complex process and low thermal conductivity. Most of the current research regarding PCMs focus on the preparation and investigation of form‐stable phase change materials (FSPCMs) 9–11 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they possess higher mechanical strength compared with organic materials. Taguchi et al 19 synthesized the microcapsules with a SiC/polyurea hybrid as the shell. The obtained phase change material showed that incorporation of inorganic particles in the shell could improve the thermal conductivity of the microcapsules.…”
Section: Introductionmentioning
confidence: 99%